DO LEADERSHIP STYLES MODERATE THE RELATIONSHIP OF ORGANIZATIONAL COMMITMENT AND BUDGETARY SLACK? AN EXPERIMENTAL APPROACH - Imas Nurani Islami; Ertambang Nahartyo (Faculty of Economics and Business, Universitas Gadjah Mada, 2019)
Introduction: this study aims to provide empirical evidence of the factors that can mitigate and encourage budgetary slack. Specifically, this study examines the effect of affective organizational commitment on budgetary slack with the style of leadership as a moderating variable. Background Problems: budgetary slack is an unethical action that often occurs in companies and little attention is given to companies that experience losses, especially when it is related to the suboptimal allocation of resources. Novelty: Previous studies paid little attention to the direct relationship between affective organizational commitment and budgetary slack. They were limited to investigating the correlation between affective organizational commitment and budgetary slack. This study provides evidence of causality between the two and includes the style of leadership as a moderating factor. Research Methods: This research is conducted through an experimental approach using a 2 x 2 between-subjects design. The participants of this research are 64 from the Master of Management (MM) program at Gadjah Mada University (UGM). Findings: The result of this study indicates that middle managers with high affective organizational commitment create a smaller budgetary slack than the middle managers with low affective organizational commitment. However, the leadership style is not proven to moderate the relationship between affective organizational commitment and budgetary slack. Conclusion: These findings provide theoretical evidence of the self-determination theory that an individual with high affective organizational commitment creates a smaller budgetary slack than an individual with low affective organizational commitment. Therefore, companies need to pay more attention to their employees’ commitment.